Growth expectations, capital flows and international risk sharing - Olli Castrén; Marcus Miller; Roger Stiegert (European Central Bank (ECB), 2003)
Over the past decades, cross-border financial flows have increased in importance and have in many occasions exceeded the underlying current account positions. This phenomenon has been accompanied by an increase in the volume of international equity transactions that accentuate the role of international risk sharing as a factor for the macroeconomic response to shocks. We use a stylised two-bloc, two-period model of the global economy, with a simple stochastic productivity shock affecting only one country. Efficient global risk-sharing imply that expected productivity gains in one country will attract equity inflows in excess of those needed to finance the current account. Upward-biased expectations about prospects for the productivity gains can further increase the risk exposure of foreign shareholders. The model is calibrated to show how ex post market losses whether due to "normal" stock market downturn or ex ante over-optimism are distributed and how they affect global consumption and current account positions. The results suggest that international spillover effects of stock market bubbles can contribute to business cycle synchronisation across economic areas.
Keywords: F41; F32; G15; 330; Capital flows; consumption smoothing; international business cycle synchronisation; international risk –sharing; risk aversion